Institutional hostility to cash and COVID-19 - Edoardo Beretta; Doris Neuberger (Universität Rostock, Institut für Volkswirtschaftslehre, 2020)
By "hostility to cash" we refer to the recent trend of incentivizing individuals towards a (privately managed) digital payment system driven by banking and financial sectors and supported by Governments. COVID-19 has on the one hand boosted this movement, with false messages about banknotes spreading the virus as a new instrument of convincement. On the other, the enduring flight to cash shows that this "relic" is even more essential in bad economic times. Restricting or eliminating cash is synonymous of welfare losses due to increased monopoly power of the financial and technology industry, reduced privacy, and threatened financial stability as a public good. As a consequence, financial exclusion and social discrimination would increase, adding to the impact of the COVID-19 crisis on inequality. By means of a logical-analytical approach combined with the newest statistical evidence and never-published comparative tables, the paper demonstrates why banknotes and coins are - all the more, in uncertain times due to SARS-CoV-2 - not otherwise substitutable, but rather a public good to be safeguarded.
Keywords: E42; E44; G21; G41; 330; banknotes and coins; COVID-19; digital payments; financial inclusion; money; payments system